2023
DOI: 10.31674/mjn.2023.v14i03.012
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge among Pregnant Women Regarding Pregnancy-Induced Hypertension at a Public Hospital in Malaysia

Abstract: Background: Pregnancy Induced Hypertension (PIH) is a significant contributor to various pregnancy complications. Therefore, an effective way to avoid possible fatal complications of the disease is to create awareness among pregnant women. Pregnant women who are aware of the danger signs of pregnancy will take responsibility for seeking medical attention if any complications arise. However, there is a lack of study done at public hospitals in Selangor regarding the knowledge level of PIH. Aim: To determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“… 42 Other researchers, however, reported no significant association between PIH knowledge/risk factors and participant’s age. 43 Teenagers are more likely to have a risk factor for PIH during pregnancy. 39 Notably, teenagers and young women use oral contraceptives to avoid pregnancy, and there is evidence that this contributes to the development of PIH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 42 Other researchers, however, reported no significant association between PIH knowledge/risk factors and participant’s age. 43 Teenagers are more likely to have a risk factor for PIH during pregnancy. 39 Notably, teenagers and young women use oral contraceptives to avoid pregnancy, and there is evidence that this contributes to the development of PIH.…”
Section: Discussionmentioning
confidence: 99%
“… 23 , 33 , 41 , 42 Other studies, like ours, revealed no significant association between respondents’ levels of knowledge and their educational status. 38 , 43 Women with a higher education, in contrast, could have better access to information, education, and communication from various sources such as the internet, books, and television, and hence may have more knowledge of PIH than women with little or no education. Kanyamura et al 50 echoes that circumstances contributing to low knowledge levels may differ for different individuals.…”
Section: Discussionmentioning
confidence: 99%
“…For many women, pregnancy and giving birth are viewed as normal and natural processes. However, some may face complications during these stages, posing risks to the health of both the mother and the baby (Khuan et al, 2023). Triple elimination in pregnant women is an important part of preventing disease transmission from mother to child.…”
Section: Introductionmentioning
confidence: 99%